Becoming Boundary Spanners in a Long-Term Engaged Scholarship Partnership - Mellinee Lesley; Amy Higgins; Elizabeth Stewart; Johanna Keene; Savannah Terry (Journal of Community Engagement and Scholarship)
Utilizing narrative inquiry, members of a school-university partnership examined the intricacies of participating in a long-term collaboration predicated upon engaged scholarship. As part of this investigation, the authors examined the convergence of different boundary spanner roles taken up by the members of the partnership and the effect of this on the goals of enacting engaged scholarship. By identifying instances that shaped their roles, commitment, and implementation of engaged scholarship, the authors captured the challenges and opportunities of sustained engagement as boundary spanners. Through a reflexive process, they identified shifts in the collaboration’s goals and outcomes, revealing pivotal ruptures or turning points in their journey. These events are argued to be crucial for their development as boundary spanners. The study emphasizes the importance of translating reflection into practice.